MINERALISASI PADA BREKSI HIDROTERMAL, DAERAH TEPU, TAMBANG EMAS TERBUKA KELIAN, KECAMATAN LINGGANG BIGUNG, KABUPATEN KUTAI BARAT, PROPINSI KALIMANTAN TIMUR - -, Antonius Bambang Yuniarto; -, Ildrem Syafri (Bulletin of Scientific Contribution, 2009)
This research was carried out at the southern pit wall in the open gold mining area of PT. Kelian Equatorial Mining, located at 00 00 '32, 56 "S - 00 05 '09, 14" South Latitude and 1150 23’ 29,02" - 1150 28' 04,73" East Longitude. Administratively, it located in the Tepu area, Subdistrict of Linggang Bigung, West Kutai, East Kalimantan province. Physiographically that area is a part of Central Kalimantan volcanic arc.Rocks exposed in this area can be divided into 4 (four) rock units, i.e. The Eocene Sandstone Unit; The Lower Miocene Andesitic Pluton Unit; The Middle Miocene Hydrothermal Breccia Unit; and The Early Miocene Diatreme Breccia Unit.Geological structures that developped in this area were joints and faults. The faults are dilational structures types, in the form of sinistral- and dextral normal faults. These geological structures facilitated the penetration of andesite, followed by the appearence of hydrothermal fluids which produced the formation of hydrothermal breccia, and diatreme breccia. Hydrothermal breccia fragment consisting of andesite and sandstone, usually in jigsaw textured which are arranged in a matrix rock flour (Sillitoe, 1985), i.e. very fine grained material that came from milling process of breccia fragments. The carbonate minerals in the form of bladed texture are dominat minerals that filled the interfragments and matrix cavities. Partially, apart of carbonate minerals, the bladed silica was also present in cavity filling. The cavity filling minerals are associated with the appearence of metallic minerals.The alteration zones in the research area can be grouped into three zones, namely: 1.) Zone containing chlorite + clay + sericite + adularia + carbonate 2.) Zone containing sericite + carbonate + clay + adularia ± quartz and 3.) Zone containing carbonate + clay + sericite + adularia + quartz / silica. These alterations are classified as subpropylitic - until phyllic zones (Corbett & Leach, 1996). Metal mineralization such as sphalerite, galena, pyrite, covellite, arsenopyrite and chalcopyrite are associated with carbonate alteration ± adularia ± quartz ± sericite ± clay were primarily formed as a cavity filling and veins in hydrothermal breccia. The analysis results of Au and Ag contents in some rocks samples of hydrothermal breccia ranged from 0.04 grams / ton to 8.96 grams / ton Ag and 0.55 to 11.8 grams / ton, while the recovery of Au ranged between 16.08% up to 85.12%. The highest content and % recovery value of Au was founded in hydrothermal breccia.The mineralization stages can be divided into three stages: 1). The pre-brecciation stage that associated with the occurence of chlorite, sericite, adularia, clay and pyrite dissemination as well as the formation of carbonate veinlets and quartzs in direction of the Northwest - Southeast, 2) The syn-brecciation stage, it related to the formation of hydrothermal breccia, i.e. the occurence of carbonate and silica enrichment and the alteration minerals such as sericite, adularia, clay that related to the deposition of base metals as cavity filling and as veinlets in the direction of Southwest-Northeast. 3) Post-breccia stage was related to the occurence of carbonate veinlets ± base metals which associated with the clay minerals. Those cut the fragments, rock flour matrix, cavities filling minerals in hydrothermal breccia after the their formation in the direction of Southwest-Northeast.Mineralization in the area of study occured as ore deposits in hydrothermal breccia and in the veins as well as the veinlets. Hydrothermal breccia formed by two processes, i.e.; structural control and high-pressure hydrothermal fluids, at the temperature more than 200° - 250° C, with the acidity condition of (pH) 6, 6-8, 3. This condition is classified as a system of low sulphidation that related to porphiry with gold-carbonate base metal deposits (Corbett & Leach, 1996).